Wildlife and natural resource management - Deal, Kevin H. (Stamford, CT, USA Cengage Learning, 2017)
"Designed for high school students enrolled in an agriculture program with a wildlife management, natural resource management, or environmental science course. This all-new fourth edition is thoroughly revised, with additional information on renewable natural resources, endangered and threatened species, wildlife management, and identification of wildlife and nonindigenous species. It is the intent of this text to present the very broad and complex subject of wildlife fisheries, and natural resource management in a manner that is interesting and understandable to the student. As our human population continues to grow, the pressure on natural resources will inevitably increase. It is therefore imperative that our young people develop an understanding and appreciation of our fish, wildlife, and other natural resources. It will be their responsibility to conserve and preserve them for future generations"--Page viii.
Glossary in English and Spanish.
Includes bibliographical references and index.
Keywords: Wildlife management; Natural resources -- Management